(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article is devoted to the life, scholarly activity, and enduring intellectual legacy of our great compatriot Mahmud al-Zamakhshari, a towering figure who earned such distinguished titles as «Jarullah» (“The Neighbor of Allah”) and «Ustadh al-Dunya» (“The Teacher of the World”). The study explores the scholar’s childhood in Khwarazm, the hardships he endured in pursuit of knowledge, and the extraordinary academic heights he attained despite a severe physical disability. Particular attention is given to al-Zamakhshari’s scholarly activities in some of the most prominent intellectual centers of the medieval Islamic world—Bukhara, Baghdad, and Makkah—as well as to his teachers, students, and scientific milieu. The article further examines his invaluable contributions to Arabic grammar, Qur’anic exegesis, and lexicography, highlighting the significance of such monumental works as «Al-Kashshaf» and «Al-Mufassal» through the lens of historical and academic sources. The study also discusses the efforts undertaken in independent Uzbekistan to research, preserve, and promote the heritage of this eminent scholar.